KEBIJAKAN LARANGAN EKSPOR ROTAN DAN PENGEMBANGAN DSAIN PADA INDUSTRI ROTAN - Sumarno - (Institut Seni Indonesia Surakarta, 2011)
Indonesia is a tropical and largest rattan producing country in the world. Such the condition in global context should become the national rattan industry superiority. However, strangely the condition in the Ã¯Â¬eld frequently shows the scarcity of rattan main material. The main material scarcity often becomes the obstacle for the national rattan industry performers, particularly in Java. This background encouraged the government to enforce the policy of rattan main material export prohibition. In order to support the main material absorption through the improvement of productivity, the government devises to develop rattan industry design. Unfortunately, it has not been mentioned in detailed how the implementation of such the design development policy is. This article belongs to a qualitative research, attempting to explain the a priori design development. The approach method used was a discourse analysis in analytical descriptive manner. The concepts of aspect design development having the most important role were marketing, designer, production. Organization trilogy in that industry included three interrelated and interdependent components. The aspect of design in domestic rattan industry includes the need for understanding, function, and comprehensive role of design among the industries.Â Keywords: rattan policy, design development, industry.